Report on the Incidence of Longer-Term Program Engagement. (Policy Papers; Policy Paper ;, 2006)
The assessments are intended to provide an analysis of the economic problems facing the member and a critical and frank review of progress during the period of Fund-supported programs, as the basis for a forward-looking assessment and strategy for future Fund engagement, including, where appropriate, an explicit exit strategy.